Process Reengineering of Fan and Blower Production - Subramaniam, Kumares Wara Rao (2004)
The most common approach to business problem solving and making improvement is by starting at the core of the business: the sequence of different elements of the business i.e. the process. The fan and blower industry is best described as job shop environment that requires different levels and process techniques. The amalgamation of all these processes and quality control system is the final desired outcome of this project. The system was designed using guidelines of the Process Quality Model (PQM). The PQM is suitable for the purpose of designing a system that will identify and document any non-conformance. The design encompasses the four major departments that are involved in production. The most important department, which is Production, consists of several sections doing their own processes. This department received through attention in order to create the optimum solution. The first step was to get the necessary comments from the employees in charge of the departments. After this, the present system is analysed to determine the current manufacturing process and its quality control measures. When this is achieved, the right definition of quality is created to be the motto for the creation of the new system. Then appropriate solutions are thought of and reworked many times to ensure they are accepted. To do this, accurate information is sent to the workers through training and education.